Use of different urea levels in the feeding of Alpine goats - Julicelly Gomes Barbosa (Revista Brasileira de Zootecnia, 2012)
The objective of this study was to evaluate intake, apparent digestibility, ingestive behavior and blood parameters of milking goats fed cactus pear (Opuntia ficus indica) and increasing urea levels in substitution to soybean meal. Ten multiparous Alpine goats with average weight of 31±6.0 kg were used and distributed into (5 × 5) Latin squares and assessed during five 17-day periods, receiving five treatments with the following substitution levels: 0; 5; 10; 15 and 20 g/kg of urea. Neutral detergent fiber (NDF), non-fiber carbohydrates, ether extract, organic matter and water intake values showed differences, whith average values ranging from 1.03 to 1.13; 0.12 to 0.14; 1.76 to 2.10 kg/day and 0.77 to 1.48 kg/day, respectively. The NDF and crude protein apparent digestibility values were significantly affected by urea levels. In relation to the ingestive behavior, the urea levels did not influence the feeding, idleness or rumination parameters. Difference was observed for the following physiological variables: feces frequency (11.5 to 15.9 times per day), urine frequency (10.8 to 14.2 times per day) and frequency of search for water (0.8 to 2.1 times per day). The urea levels influenced the blood parameters, whose average levels ranged from 29.83 to 40.76 mg/dL. Pear cactus and increasing urea levels in substitution to soybean meal do not alter the dry matter intake or ingestive behavior. The use of urea associated with forage cactus reduces water intake and increases the blood urea concentration of milking goats.